Ernst L. Wynder: A Pioneer of No Tobacco World (Epidemiology, Biostatistics, and Public Health, 2022)
Ernst L Wynder was a great epidemiologist who devoted his career to investigate harmful effects of tobacco smoke, in particular his studies represent a landmark in the history of epidemiological research on lung cancer.The commitment of Ernst Wynder was not limited to the risk factors related to tobacco. In fact, he studied also the role of nutritional factors in the incidence of tumors.His talent, enthusiasm and tireless energy have allowed him to obtain a complete victory despite the difficulties and the initial loneliness.